TOE Framework and Social Media Adoption: Effects on Indonesian SME’s Digital Performance - Della Ayu Zonna Lia; Raisa Fitri; Rayie Tariaranie Wiraguna; Handri Dian Wahyudi (University of Merdeka Malang, 2025)
This study looks into how social media adoption is impacted by organizational, technological, and environmental (TOE) factors and how that affects the performance of small and medium-sized businesses (SMEs) in Indonesia. As pivotal elements of the national economy, constituting over 60% of GDP and 97% of employment, SMEs are under increasing pressure to adopt digital transformation. Nonetheless, their utilization of social media is often restricted by inadequate technological capabilities, organizational preparedness, and external environmental obstacles. In order to investigate how these factors affect the integration of social media into corporate operations and ascertain whether such adoption improves firm performance, this study makes use of the TOE framework. A quantitative methodology is utilized, with data gathered via online surveys distributed to SME proprietors throughout Indonesia. Findings show technological readiness boosts social media adoption (SMA), but the technological factor (TF) negatively impacts SME performance (SMEP), suggesting complex tech creates 'technostress.' The organizational factor (OF) doesn't affect SMA, but positively impacts performance via teamwork and communication (supporting RBV). The environmental factor (EF) strongly and positively influences both SMA and SMEP, reflecting high market competition. Crucially, SMA does not mediate the TOE-performance link, as SMEs use it reactively, without a strategy. In summary, while technology and environment drive adoption, sustainable performance hinges on organizational capability and an integrated digital strategy. This study's results provide useful information for policymakers, practitioners, and technology providers to promote inclusive digital growth and make the economy more resilient.